A preliminary study of course information on i-Learn perspectives : focusing in accessibility, contents and user interface parameter / Noor Saadah Sulaiman - Sulaiman, Noor Saadah (Faculty of Computer and Mathematical Sciences, 2007)
Nowadays every people can accept the fact that computer has become an important tool in daily life. The computer is used from preschool, followed by primary school, secondary school, higher education up till the working environment. The computer system is use as the tool for students and lecturers to interact. So as the highest level education, Mara University of Technology (UiTM) has built one system that can be used by all lecturers and students in education and also too many international universities. One of the systems is i-Learn portal that contributed from e-learning system. i-Learn portal that include with the course information is used to give lecturers and students the information about courses and subject. With this i- Learn portal it can help students to finding more information about the course and the schedule that related with that subject. This project is a survey study on the course information through i-Learn perspective that focusing on accessibility, content and user interface parameter. This study is need because as a new features system it needs the respond from the user about the characters of system especially on content, accessibility and user interface whether it suitable or not and their feedback as a users. Before i-Learn course information is develop the lecturers and students only used the manual course information that make difficult to conduct. The instruments used in this project are questionnaires, which are distributed to the lecturers. About 150 respondents participate in this research. Based on the analysis of the data, it is discovered that i-Leam course information will influence lecturers about their teaching method and the important of the course information through i-Learn. There also the recommendation that with i-Learn course information it can make the lecturers job become easy and faster